Incorporation of Hydroxamate Siderophore and Associated Fe Into Marine Particles in Natural Seawater - Lin, Peng; Xu, Chen; Sun, Luni; Xing, Wei; Santschi, Peter H. (Frontiers in Marine Science, 2020)
Microorganisms produce soluble low-molecular-weight (LMW, <1 kDa) siderophores, one of the strongest Fe-binding agents, to respond to the scarcity of Fe in the ocean. The presence of siderophores in marine particles/colloids is mostly not considered. Here, experimental evidence is provided to suggest the possibility of siderophore incorporation into marine particles. An incubation experiment with a 59Fe-complexed desferrioxamine (DFO, siderophore-model compound) was conducted using natural seawater (<3µm) at dark condition to examine the size re-distribution of DFO and its associated Fe during microbial growth. 59Fe and DFO in suspended particles/aggregates, colloids and dissolved phase were quantified after the incubation. Our results showed that ~55% of the 59Fe, originally in the form of LMW DFO-Fe, was incorporated in the suspended particles/aggregates. Noticeably, a minor amount (0.395±0.020%) of the DFO was incorporated into the particulate phase. This finding is novel in that while the DFO facilitating Fe incorporation into microbial biomass was released back into the dissolved phase, still a minor fraction of the siderophores could be ‘retained’ in particles. This could have become cumulatively more important in more complex natural systems that involves the interplay between minerals, bacteria, phytoplankton and zooplankton. Furthermore, our results indirectly suggest a balance of the two different mechanisms during the Fe-siderophore transport. Our results are in favor of the processes occurring outside of the cells (Fe dissociation from the Fe-siderophore complex followed by the microbial Fe uptake) but the second mechanism can also exist (uptake of intact Fe-siderophore complex into the microbial intracellular fractions), albeit to a lesser extent.